Low‐Pass Features of Optical Nano‐Filters Constituted by Simple Layered Structures. Issue 9 (27th June 2013) - Valagiannopoulos, Constantinos A.; Sihvola, Ari
ABSTRACT Low‐pass filtering in the nanoscale is a significant procedure that has recently attracted considerable attention due to the upsurge of state‐of‐the‐art nanophotonic applications. In this work, two consecutive dielectric layers with specific permittivity combination and certain size ratio are found to exhibit good performance as a low‐pass filter in the visible and at the nano‐frequencies. Despite its simplicity, the device retains a satisfying stability in terms of total transmission at the low frequencies; simultaneously, it is impenetrable for signals containing higher frequencies and is characterized by a lack of electromagnetic resonances. Several graphs verify these beneficial features of the structure and further conclusions related to its operation and functionality are obtained. © 2013 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:2099–2106, 2013